2020
DOI: 10.1039/c9gc03992a
|View full text |Cite
|
Sign up to set email alerts
|

A dual biomimetic process for the selective aerobic oxidative coupling of primary amines using pyrogallol as a precatalyst. Isolation of the [5 + 2] cycloaddition redox intermediates

Abstract: Low-cost pyrogallol precatalyst undergoes an oxidative self-processing step for delivering the active organocatalyst in situ through a dual biomimetic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 96 publications
1
13
0
Order By: Relevance
“…In contrast, the reactions of the aliphatic amines were inefficient under the same conditions, such that only trace or no target imines were detected (Table 3, entries 1p-1s), most aliphatic imines are scarcely stable because they are easily isomerized into enamine tautomer which decomposed under air. [39] For most aromatic amines investigated here, the catalytic efficiency of CoCl 2 Á6H 2 O was comparable with or higher than the reported efficiencies with the other metal catalysts (such as Cu, [20] Ru, [15] Au, [17] V [23] ) and Co complexes. [34] Interestingly, for the heteroaromatic methanamine, the catalytic data mentioned above have indicated a higher efficiency compared with the previously reported catalysts.…”
Section: S C H E M E 1 Control Experiments For the Mechanistic Studiessupporting
confidence: 68%
“…In contrast, the reactions of the aliphatic amines were inefficient under the same conditions, such that only trace or no target imines were detected (Table 3, entries 1p-1s), most aliphatic imines are scarcely stable because they are easily isomerized into enamine tautomer which decomposed under air. [39] For most aromatic amines investigated here, the catalytic efficiency of CoCl 2 Á6H 2 O was comparable with or higher than the reported efficiencies with the other metal catalysts (such as Cu, [20] Ru, [15] Au, [17] V [23] ) and Co complexes. [34] Interestingly, for the heteroaromatic methanamine, the catalytic data mentioned above have indicated a higher efficiency compared with the previously reported catalysts.…”
Section: S C H E M E 1 Control Experiments For the Mechanistic Studiessupporting
confidence: 68%
“…We surprisingly found that non-negligible amount of benzoic acid (22%, 7) was also formed when 4-phenylbutyl benzimidazole (5) was subjected to the reaction and corresponding carboxylic acid 6 was isolated in 40% yield, while benzimidazole 2a was obtained in 71% yield. However, a trace amount of benzoic acid was detected when 4-phenylbutanoic acid 6 (or butylbenzene, 8) and 2-methylbenzimidazole (1j) were mixed under the standard conditions.…”
Section: Synthesis Papermentioning
confidence: 92%
“…The data match with literature. 11 2-Heptyl-1-methyl-1H-benzo[d]imidazole (1p). Following general procedure, o-phenylenediamine (216.0 mg, 2.0 mmol) and octanoic acid (288.4 mg, 2.0 mmol) were selected as the substrates.…”
Section: -Methyl-2-pentyl-1h-benzo[d]imidazole (1o)mentioning
confidence: 99%
See 2 more Smart Citations